G107(P) Infantite spasms: Management in resource limited countries. (27th April 2016) - Sultan, Tipu; Rafique, Sajad
Abstract : Objective: To compare the outcome of ACTH with oral prednisolone for treatment of infantile spasms. Methodology: This is a randomised controlled trial conducted at department of Paediatric Neurology, The Children Hospital, Lahore, Pakistan after ethical approval from January 1 st 2013 to November 1 st 2015. Seventy patients with infantile spasms were randomised in two equal groups of 35 patients in each group. Patients in group A received prednisolone (2mg/kg/day for 4 weeks followed by tapering over next 4 weeks) and in group B received ACTH (250 IU/m square/day) for two weeks followed by tapering over next 4–6 weeks. The two groups were compared for the spasms free period. Statistical significant determined by chi-square test (p < 0.05 was taken as significant). Non-probability purposive sampling was used and an inclusion criterion was children up to age of 5 years with infantile spasms. Exclusion criteria include children who had been previously treated with steroids or ACTH. Seventy patients fulfilling inclusion criteria were enrolled through neurology department of Children Hospital, Lahore. History, informed consent was taken by parents and was divided in two groups by lottery method. All the information was collected on a specially designed proforma. Results: In group A, 80% patients were spasms free, while in group B, 75%) patients were spasms free. Conclusion: Oral prednisolone is as good as ACTH in control of seizures and much cheaper.